(untitled) (Journal of Technology Research, 2025)
The continuous pursuit of efficiency in mechanical design demands components that combine lightweight characteristics with structural strength.This study presents an integrated Computer-Aided Design (CAD) and Finite Element Analysis (FEA) workflow for the topology optimization of a mechanical component, where an L-shaped bracket was selected as a case study.The process began with the initial design and static structural analysis using SolidWorks to establish a baseline performance under typical operating loads.The model was then subjected to a topology optimization study in SolidWorks Simulation, aiming to reduce mass while maintaining structural integrity within predefined constraints. After interpreting the optimization results, the optimized geometry was reconstructed in SolidWorks, and a final validation FEA was performed on the new design.The results demonstrated a 54.74% reduction in mass compared to the original model, while the maximum von Mises stress increased by only 15%, remaining well below the yield strength of the alloy steel. This confirms the effectiveness of topology optimization in achieving substantial weight reduction without compromising key performance criteria, emphasizing its essential role in modern mechanical design and analysis.